Unexplained diarrhoea and failure to thrive in 2 siblings with unusual facies and abnormal scalp hair shafts: a new syndrome. Issue 3 (March 1982) - Stankler, L; Lloyd, D; Pollitt, R J; Gray, E S; Thom, H; Russell, G
Abstract : A family is described in which 2 siblings born to healthy parents presented with abnormal facies, persistent diarrhoea, and early death. Exhaustive pathological and biochemical investigations failed to find a cause. The scalp hair of both babies had an abnormal amino-acid composition, and presented an appearance that was unique on scanning electron microscopical examination; this fact and the clinical picture probably represents a new syndrome.